Plasma-Treated Water Retards Pellicle-like Biofilm Formation of Bacillus subtilis - Thomas Weihe; Jan Wallis; Mareike Meister; Jörg Ehlbeck; Uta Schnabel (Microbiology Research)
Plasma-treated water (PTW) recently entered science as a sanitizing agent, which possess the capability for on-demand production. It offers interesting possibilities for sustainable and resource-saving applications in healthcare and food production. The present study monitors the impact of PTW on suspended cells before the biofilm formation of the putrefactive bacterium B. subtilis. Light and electron microscope imaging captures the maturing of growing biofilms within the first 24 h. Microbiological assays (proliferation, LIVE/DEAD, and XTT), which mirror the proliferation of the bacterium, the metabolic activity, and the integrity of the cell membrane, underpinning the metabolic response of still-suspended cells. B. subtilis cells without any treatment build up a resistive biofilm within the 24 h. Cells that remain in the supernatant predominantly appear as monomers or dimers. Treated B. subtilis cells have hampered biofilm formation and were not able to build up a confluent growing biofilm within the first 24 h. Moreover, the microscopic observation of PTW-treated suspension showed cellular aggregates with an unusually high connectivity of the individual cells. The findings suggest this cellular reaction as a counter measure against the adverse impact of PTW treatment. The experiments show the adverse impact of PTW on B. subtilis–biofilm formation and the phenomenological reaction of B. subtilis.